2017
DOI: 10.1016/j.celrep.2017.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Islet Blood Flow Dynamics in Primates

Abstract: SummaryBlood flow regulation in pancreatic islets is critical for function but poorly understood. Here, we establish an in vivo imaging platform in a non-human primate where islets transplanted autologously into the anterior chamber of the eye are monitored non-invasively and longitudinally at single-cell resolution. Engrafted islets were vascularized and innervated and maintained the cytoarchitecture of in situ islets in the pancreas. Blood flow velocity in the engrafted islets was not affected by increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 35 publications
2
36
1
Order By: Relevance
“…Using an in vivo platform in non‐human primates, Diez et al transplanted islets autologously into the anterior chamber of the eye and monitored them non‐invasively and longitudinally at single‐cell resolution. Their investigation found that blood flow to islets is dynamic and is controlled by a vasoconstriction of the capillaries, potentially under the control of autonomic innervation . This study also demonstrated no changes in velocity with glucose or the GLP‐1 analog, liraglutide; in contrast to the findings of previous studies in the rodent pancreatic model …”
Section: Intravital Imaging Visualizes In Vivo Cellular Dynamics and contrasting
confidence: 60%
“…Using an in vivo platform in non‐human primates, Diez et al transplanted islets autologously into the anterior chamber of the eye and monitored them non‐invasively and longitudinally at single‐cell resolution. Their investigation found that blood flow to islets is dynamic and is controlled by a vasoconstriction of the capillaries, potentially under the control of autonomic innervation . This study also demonstrated no changes in velocity with glucose or the GLP‐1 analog, liraglutide; in contrast to the findings of previous studies in the rodent pancreatic model …”
Section: Intravital Imaging Visualizes In Vivo Cellular Dynamics and contrasting
confidence: 60%
“…Furthermore, the exposed location of the islets in the eye allows for manipulation by local treatment or, for that matter, light, and can illustrate, for example, the effects of parasympathetic innervation [ 23 , 54 ]. In addition, non-human primates can be used as both donors and acceptors for islet transplantation to the anterior chamber of the eye to study non-rodent islet physiology in vivo [ 71 ]. In vivo imaging of islet vasculature [ 71 73 ] and islet function [ 69 , 70 , 74 ] have been performed successfully in anaesthetised animals, specifically, the mouse [ 69 , 70 , 72 74 ] and non-human primate [ 71 ].…”
Section: How To Further Investigate Alpha Cell–beta Cell Interactionsmentioning
confidence: 99%
“…Moreover, neurons and vascular supplies re-wire ( Rodriguez-Diaz et al . 2012 , Diez et al . 2017 ), affording the opportunity to investigate the influence of these on beta cell heterogeneity, and function/fate/plasticity can be followed longitudinally in the same animal (e.g.…”
Section: New Tools For Understanding Beta Cell Heterogeneitymentioning
confidence: 99%